The Effect of Compensation and Digital Literacy on Performance in Village Apparatus in Karangtengah District, Cianjur Regency - Widyani, Alvia; Sary, Fetty Poerwita (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Indonesia has a tiered government structure from the national to local levels, where village governments play a strategic role in regulating and managing national development interests. The village head, as a leader elected by the community supported by the village apparatus, has a strategic role in realizing good public services at the village level. The quality of service and the achievement of village development targets are highly dependent on the optimal performance of village apparatus. However, based on data and interviews with village officials in Karangtengah District, Cianjur Regency, it was found that the phenomenon of complaints such as inadequate compensation and low digital literacy is still one of the obstacles in optimizing the performance of village officials in Karangtengah District, Cianjur Regency. This study aims to find out how compensation and digital literacy affect the performance of village apparatus in Karangtengah District, Cianjur Regency both simultaneously and partially. This study uses a quantitative method approach, with the purpose of research being causal descriptive. Data was collected through a survey from a sample of village apparatus taken from 16 villages as many as 118 people, then analyzed using the Partial Least Square Structural Equation Model (PLS-SEM) method to test the relationship between the variables studied. It is hoped that the results of this study can show that compensation and digital literacy have a significant influence on the performance of village apparatus. Thus, this research can make an important contribution to local governments in formulating policies that can support increasing compensation and digital literacy of village officials. With this policy, it is hoped that village officials will be able to work more optimally in providing services to the community.